2012
DOI: 10.1155/2012/838420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Acupuncture on Disuse Osteoarthritis: An Ultrasound Biomicroscopic Study of Patellar Articular Cartilage in Rats

Abstract: To investigate the effect of laser acupuncture (LA) on disuse changes in articular cartilage using ultrasound biomicroscopy (UBM), Eighteen rats were randomly divided into the control group (C), the tail-suspended group (T), and the tail-suspended with LA treatment group (L). During 28-day suspension period, group L were treated with LA at acupoints on the left hindlimb while group T had a sham treatment. Ultrasound roughness index (URI), integrated reflection coefficient (IRC), integrated backscatter coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…The cartilage results of this study are similar to those of previous study showing that disuse-induced significant changes in the cartilage tissue [ 25 ]. However, disuse simultaneously induced cartilage degradation and bone loss [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…The cartilage results of this study are similar to those of previous study showing that disuse-induced significant changes in the cartilage tissue [ 25 ]. However, disuse simultaneously induced cartilage degradation and bone loss [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Guo et al [ 64 ] proved that laser irradiation on KI-1 and ST-36 could inhibit bone loss in rats caused by skeletal unloading via a systemic regulation. Besides, in their further investigation [ 65 ], they suggested that unloading-induced cartilage degeneration in rats can be reversed by the same laser therapy. KI-3 and BL-60 are located on either side of the Achilles tendon and are a common acupoint combination for the treatment of pain in the lower back, legs, and feet.…”
Section: La On Single Pointmentioning
confidence: 99%